Numerical simulation of wastewater discharge into water objects to improve discharge devices - Lyubimova, Tat’yana Petrovna; Lepikhin, Anatoliy Pavlovich; Parshakova, Yanina Nikolayevna (Computational Continuum Mechanics, 2019)
The expansion of salts extraction and production has created a need for new spent brine disposal methods. This task is complicated by the fact that “heavy” brines due to the suppression of vertical turbulent pulsations can spread over considerable distances without a significant reduction in their concentration. Based on numerical modeling, we put forward some suggestions for optimizing exhaust structures designed to discharge the wastewater containing heavy impurities. The calculations performed in the framework of a three-dimensional statement for various conditions of discharge of wastewater show that the structures which provide for the location of exhaust devices near the surface of the reservoir turned out to be the most effective ones. However, such structures are difficult to implement in a certain reservoir section. Easy-to-implement and at the same time quite effective is a scheme that includes bottom arrangement of exhaust devices and selective intake of highly saline wastewater from sludge storage facilities. Regardless of the selected scheme for the disposal of highly mineralized wastewater, their discharge must be carried out in strict coordination with the hydrological regime of the water intake. This will provide the most efficient use of the assimilative capacity of a water body and the best way to reduce environmental stress.
Keywords: wastewater; heavy impurity; three-dimensional numerical simulation; dilution of highly saline wastewater